ANEMIA AS A COMMON COMORBIDITY AND PROGNOSTIC MARKER IN HEART FAILURE : Anemia and heart failure - Ćirić-Zdravković, Snežana; Koraćević, Goran; Stanojevic, Dragana; Djindjic, Boris; Petrović-Nagorni, Svetlana; Nagorni, Ivan; Nagorni, Miloš; Perišić, Jelena (Acta medicae Medianae, 2025)
Heart failure (HF) is a clinical syndrome characterized by the inability of the heart to pump the amount of blood necessary to meet the body’s needs for oxygen and energy substances in proportion to physical activity, provided that the venous blood flow to the heart is preserved. The frequency of HF and left ventricular dysfunction increases with the age of patients. It is considered that the diagnosis of heart failure is the most common discharge diagnosis at the age of 65. Comorbidities are very important in HF patients for several reasons. Chronic anemia is very often associated with HF (up to 55% of patients). The aim of the work was to assess the presence of anemia in patients with HF and its impact on the prognosis of these patients. The total number of subjects was 201. Anemia was more common in women than in men and was equally prevalent in systolic and diastolic HF, which is also consistent with previous reports. However, anemia was not more common in elderly HF patients. Patients with New York Heart Association (NYHA) class IV HF were significantly more likely to have anemia than those with NYHA class I or II, which is consistent with previous reports. In patients with HF, there is a significant frequency of anemia as non-cardiac comorbidity. The presence of anemia significantly impacts the hospital and post-hospital course. Therapy should be started even with subclinical anemia or with reduced iron depots even though the hemoglobin is still within the reference values because this improves the prognosis of our patients.